PENGARUH KOMPETENSI DAN KARAKTERISTIK INDIVIDU TERHADAP KINERJA KARYAWAN DENGAN MEDIASI MOTIVASI KERJA (Studi Pada Karyawan PT. Nayati Indonesia, Semarang). (Jurnal Mahasiswa Pasca Sarjana, 2015)
This research investigates and examines The Influence of Competency and Individual Characteristics on Employee Performance by Using Motivation as Mediating Role in PT. Nayati Indonesia Semarang.This research uses census method as sampling technique. The collected sample is 105 respondents. The measurement instrument consists of validity and reliability test with the crobach alpha value. Model measurement uses coefficient determination and F test. The hypotheses test uses linier regression and t test.The result of this research found that Competency positively and significantly influences Motivation, Individual Characteristics positively and significantly influences, Competency has positive and significant effect on Employee Perfomance, Individual Characteristics has a negatice and non significant eftect on Employee, Motivation has a negative and non significant effect on Employee Perfomance.Key Words: Competency, Individual Characteristics, Motivation, Employee Perfomance.